ORGANISASI MASYARAKAT (ORMAS) DOMPET DHUAFA DALAM PERSPEKTIF PEMBERDAYAAN MASYARAKAT - Mulyadi, Mohammad (Jurnal Aspirasi, 2012)
Community Empowerment Program is not just the responsibility of the government in tackling social problems in a community. Community Empowerment is also the responsibility of all parts of the nation, including community organizations. This conceptempha sizes empowerment to create a self-sufficient community. Orphanage’s Purse (Dompet Dhuafa) is one of many community organizations in Indonesia and now has spent quite alot of community empowerment efforts. Some of them are health care and education to name but a few.